An Educational Training on Cervical Cancer Screening Program for Rural Healthcare Providers in India - Isaac, Rita Caroline; Ramamurthy, Prashanth; Finkel, Madelon; Kunjuvareed, Annie Illikal; Trevena, Lyndal (Indian Journal of Community Health, 2014)
Conventional, cytology based Cervical cancer screening programmes used in the developed world is often not practical in developing countries. Training of health care work force on a feasible, low-tech, screening methods is urgently needed in low resource settings. Twenty providers including doctors and nurses participated in a 2-days training workshop organized by a Community Health Center in rural South India. The pre-post-training assessment showed significant improvement in knowledge about cervical cancer, ‘low tech’ screening, treatment options and counseling among the participants. Twenty volunteers screened at the workshop, 2 women (10%) tested positive and one had CINIII lesion and the other had cervical cancer stage IIIB. After the training, the participants felt confident about their ability to counsel and screen women for cervical cancer.